Co-production of a physical activity referral scheme in the German healthcare system - Geidl, Wolfgang; Klamroth, Sarah; Mino, Eriselda; Weißenfels, Anja; Naber, Inga; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (International Society for Physical Activity and Health (ISPAH) Congress 2024, 2024)
Background: Physical activity referral schemes (PARS) have the potential to promote physical activity (PA) among the mostly inactive primary care population with non-communicable diseases (NCD). No PARS has yet been structurally implemented in the German primary care system. Purpose: The research project BewegtVersorgt aims to develop, implement and evaluate a PARS to promote PA for persons with NCD within the German healthcare system. Methods: The PARS was developed using a co-production approach which integrated twelve organizations from different sectors (health insurances, physicians, exercise professionals, patients’ representatives). Three co-production meetings were applied where individual ideas and current evidence were combined, and different PARS models were elaborated. Finally, all stakeholders agreed on one PARS for implementation as a regional model project and seven stakeholders were purposefully selected for interviews to evaluate the co-production process. Results: The co-produced PARS starts with the primary care physician who offers PA advice and afterward refers patients to an exercise professional. The exercise professional delivers the remaining components of the intervention: initial assessment, six 1-hour individual PA counselling sessions, final assessment. From stakeholder perspective, the following factors were highlighted as facilitators of the development process: co-production approach, process of co-production, multi-sector stakeholder group, possibility of active participation, coordinating role of researchers, communication, atmosphere and interaction. In contrast, differences in roles and hierarchy, merging of different perspectives, clarification of intervention costs, and competition and conflicting interests were pointed out as challenges. Conclusions: By using the co-production approach, it was possible to develop a new PARS and implement it as regional model project in routine practice. Practical implications: Co-production is a beneficial approach for the development of PARS intended for integration into healthcare systems. Support/Funding Source: The study is funded by the Federal Ministry of Health based on a resolution of the German ‘Bundestag’ by the federal governmen